The Role of Greenways for Cultural and Historical Continuity in New Urbanism: A Case Study for Halic - Zerrin Hosgor; Reyhan Genli Yigiter (European Regional Science Association (ERSA), 2006)
Urban open spaces present the good quality of life to communities. Open space systems must be considered as a sub-system of the urban infrastructure for creating the livable cities and the sustainability in rapid urban growth process. It has accepted to determine the necessities of some policies, finance managements and application tools to build the green infrastructure. When Istanbul metropolitan city has been investigated in this concept, some requirements that need functional and spatial connectivity, environmental protection and recreational opportunities for citizens appear in the environmentally insufficient areas. The landscape planning that will respond these negativenesses, present some solutions, provide some opportunities and prevent disappearance of the urban open spaces constitutes the conceptual framework of this study. In the last two decades, the modern landscape planning concept that called "greenway planning" in 21. century, the planners concern this concept with the aims of the nature protection that balances for both conservation and growth, creating livable environment and maintain open spaces. By enriching the existing green spaces and increasing their uses, helping to emphasize the values of the poor resources and linking them with each other. The firstly aim of the study is to define the greenway concept that is useful for urban metropolis. Greenway that is a special kind of linear landscape, represent the potential linking landscape features as historical/cultural, natural and recreational. Greenways has become a tool to reach the natural life by providing linkage to housing and parks, by saving unique elements of the natural and cultural heritage that is important for public recreation in this century. The second aim of the study is to define a methodology that is useful for greenway planning for Istanbul by adopting from planning methods in Europe and America to create areas that provide recreational an environmental benefits and the places that people escape from the urban stress of the daily life in there. After explaining the opportunities and benefits of the greenway for urban settlements, in this study the main purpose is to define the greenway like a solution and examine the feasibility of greenway that links the natural resources, parks, historical and cultural sites with each other or residential areas in some situations for Istanbul metropolitan city in which the green areas are disappeared with urbanization pressure. It was determined the planning principles in application phase by investigating the applied projects, concluded the study in local scale and emphasize Halic greenway plan like the beginning of the whole greenway plan of Istanbul.
Keywords: 330